The Effect of Rainwater in Concrete Mixture on Concrete Compressive Strength - Siregar, Adde Currie; Liana, Ulwiyah Wahdah Mufassirin; Yatnikasari, Santi; Agustina, Fitriyati; Rahma, Annisa (JURUSAN TEKNIK SIPIL, 2023)
Rainwater was acidic water and had a pH generally ranging from pH 5.2 to 6.5. In this research using quantitative research types, where the data was obtained by conducting research in the laboratory. The sample used a cylindrical concrete with a size of 15 x 30 cm with a total of 30 specimens that will be tested for compressive strength with a Machine Compression testing machine to determine the compressive strength of concrete. The results of this study were the compressive strength of concrete using rainwater pH 5.8 and normal PDAM water pH 7.0 as a comparison. The results showed of compressive strength with water pH 7.0 at the age of 3 days 6,638 MPa, 7 days 11,878 MPa, 14 days 17,567 Mpa, 21 days 19,840 MPa and 28 days 21,490 MPa. While the results of compressive strength with rainwater pH 5.8 at the age of 3 days are 9,107 MPa, 7 days 13,830 MPa, 14 days 16,425, 21 days 16,470 and 28 days 17,982 MPa. From the results of the compressive strength above, it can be concluded that the use of rainwater pH 5.8 in concrete mixtures and curing at the age of 28 days had decreased in compressive strength by 16,32% of the compressive strength of PDAM water. Which indicates that PDAM water pH 7.0 was better for mixing concrete and curing compared to rainwater pH 5.8.